Durability and field condition study of seal of SAVY-4000 storage container. (March 2014) - Weis, E. M.; Blair, M. W.; Hill, B. D.; Stone, T. A.; Smith, P. H.; Winter, J. C.; Reeves, K. P.; Veirs, D. K.
<x content-type="archive" xml:space="preserve">Abstract</x> The conditions of use for rubber O-rings are at least as important as their physical properties in their effect on the quality of a seal. Under normal use conditions, O-rings may be subject to wear and environmental contaminants such as hair and dirt. This study examines how these factors impact the leak tightness of a nuclear material storage container and the likelihood of the inadvertent release of radioactive material. The durability lifetime of an O-ring was explored by opening and closing four SAVY-4000 1 quart containers 100 times and periodically performing helium leak testing, though no significant change in leak rate was observed. This study also explored how the accumulation of dust or hair on the O-ring surface would affect the leak rate of the containers. A single hair crossing the seal, or a sufficient amount of particulate matter would compromise the seal, but after cleaning, the seal was re-established.